Seismic Tomography and Earthquake Relocation in North China Craton From 2008 to 2017 - Wu, Bateer; Ma, Tian (Frontiers in Earth Science, 2022)
We present a newly developed three-dimensional seismic velocity model and high-precision earthquake relocations in North China using seismic data recorded by the National Earthquake Data Center of China from 2008 to 2017 through the double-difference tomography (tomoDD) method. The Vp model in the upper crust (below 15 km) generally agrees with those in previous studies, and it fits well with the geological structure. The result shows that the vast majority of earthquakes in North China occurred at the junction of the low-velocity zone (depression zone) and the high-velocity zone (uplift zone). This situation is difficult to change in the short term, so it is highly unlikely that another earthquake of the magnitude of 7.2 in Xingtai in 1966 and 6.2 in Zhangjiakou North in 1998 will occur in these areas in the near future. But in the Tangshan earthquake area, the situation is completely different. Our joint inversion results of 3D P-wave velocity structure and earthquake relocation show that there is a narrow low-velocity anomaly perpendicular to the surface at 20–25 km in the Tangshan area and there are no earthquakes in this anomaly area. The formation of this low-velocity zone is most likely due to the remnants of the delayed subduction of the Pacific plate to the Eurasian plate, and in the context of the Kobe earthquake in Japan, we believe that this anomaly will continue to erode the Tangshan subsurface structure and may cause strong earthquakes in the future. Our study provides the groundwork for future earthquake prevention and mitigation in North China.